2007
DOI: 10.1007/s10653-007-9112-2
|View full text |Cite
|
Sign up to set email alerts
|

Contamination indices and heavy metal concentrations in urban soil of Ibadan metropolis, southwestern Nigeria

Abstract: An assessment was conducted on soils of Ibadan metropolis using geochemical approach in order to establish the concentration of heavy metals and develop geoaccumulation index maps. Petrographic studies and X-ray diffractograms showed that soils of Ibadan were derived from the weathering of the bedrocks. The concentrations of Cu, Pb, and Zn were found to be greater in soils more than the background. Positive correlation occurred between Cu, Pb, and Zn indicated a common anthropogenic source in the soil while Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 19 publications
2
35
1
Order By: Relevance
“…In the last three decades the geochemistry of soil contaminants (particularly heavy metals) in a number of cities has been studied, such as Minneapolis, USA (Mielke et al 1984); Aberdeen, Scotland (Paterson et al 1996); Birmingham, England (Wang et al 1997); Berlin, Germany (Birke and Rauch 2000); Tallinn, Estonia (Bityukova et al 2000); Seville, Spain (Madrid et al 2004); Gainesville and Miami, Florida, USA (Chirenje et al 2003); Montana, USA (Burt et al 2003); Gibraltar (Mesilio et al 2003); Japan (Takeda et al 2003); Wolverhampton, England (Hooker and Nathanail 2006); and Ibadan, Nigeria (Odewande and Abimbola 2008). In recent years, China has also conducted such investigations; for example, Chen et al (2005) reported the Cu, Ni, Pb, and Zn contamination status in urban park soils in Beijing.…”
Section: Introductionmentioning
confidence: 99%
“…In the last three decades the geochemistry of soil contaminants (particularly heavy metals) in a number of cities has been studied, such as Minneapolis, USA (Mielke et al 1984); Aberdeen, Scotland (Paterson et al 1996); Birmingham, England (Wang et al 1997); Berlin, Germany (Birke and Rauch 2000); Tallinn, Estonia (Bityukova et al 2000); Seville, Spain (Madrid et al 2004); Gainesville and Miami, Florida, USA (Chirenje et al 2003); Montana, USA (Burt et al 2003); Gibraltar (Mesilio et al 2003); Japan (Takeda et al 2003); Wolverhampton, England (Hooker and Nathanail 2006); and Ibadan, Nigeria (Odewande and Abimbola 2008). In recent years, China has also conducted such investigations; for example, Chen et al (2005) reported the Cu, Ni, Pb, and Zn contamination status in urban park soils in Beijing.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported the contamination of heavy metals in urban soils (Biasioli et al 2006(Biasioli et al , 2007Chen et al 1997Chen et al , 2005Chirenje et al 2004;Chon et al 1995;Chung and Li 2002;Imperato et al 2003;Kelly et al 1996;Lee et al 2006;Li et al 2001;Linde et al 2001;Lu et al 2003;Madrid et al 2002;Manta et al 2002;Möller et al 2005;Morton-Bermea et al 2008;Odewande and Abimbola 2008;Paterson et al 1996;Pichtel et al 1997;Sanchez Martin et al 2000;Thuy et al 2000;Wilcke et al 1998). These studies have provided valuable information about possible contamination of heavy metals in urban soils, including chemistry, mobility and bioavailability of the heavy metals in the urban environment.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of similar studies in Nigeria (Onianwa et al 2003;Iwegbue et al 2006;Odewande and Abimbola 2008), but these studies may be limited by not generating enough geographical widespread dataset of various artisan activities that are typical of urban cities of developing countries. Besides, the studies were conducted in reasonably industrialized regions of Nigeria, and this might have interfered with the investigated anthropogenic activities.…”
Section: Resultsmentioning
confidence: 99%